Multi-scale characterization of the spatial distribution of movable hydrocarbon in intersalt shale of Qianjiang Formation, Qianjiang Sag, Jianghan Basin - Zhongliang SUN; Furong WANG; Yuanjia HAN; Yuguang HOU; Sheng HE; Jing LUO; Youheng ZHENG; Shiqiang WU (Shiyou shiyan dizhi, 2020)
Pore space containing mobile shale oil was more precisely characterized by comparing the change of adsorption volume of low-temperature nitrogen experiments and the change of mercury intake volume in high-pressure mercury injection experiments and the change of pore diameter using field emission scanning electron microscopy. The Eq34-10 rhythmic mobile hydrocarbon mainly occurs in dolomitic intercrystalline/intergranular pores and clay mineral interbedded pores, and movable hydrocarbon is relatively rich in lamellar shale. Low temperature nitrogen adsorption and high-pressure mercury injection measurements of pore size were spliced with pore size of 80 nm, and the results showed that movable hydrocarbon mainly occurs in the range of pore size less than 200 nm, and also occurs in the micron sized pores. Relatively more movable shale oil occurs in pores from 90 nm to 200 nm. The samples with low clay mineral content can yield movable hydrocarbon within the pores of ≤5 nm. The higher the porosity, the larger the average pore size, and the richer the movable shale oil.